Electronic Based Archive Management at the Office of PT. Jasa Raharja Makassar - Akib, Haedar; Saleh, Sirajuddin; Nisaa, Andini Khoirun; Isgunandar, Isgunandar (Universitas Negeri Makassar, 2022)
Archives role an important role in the smooth running of organizational activities, namely as a source of information and as a memory center for members of the organization. This study aims to determine how the management of electronic archives at the PT. Makassar Grace Service. To find out these objectives, the researchers set 3 (three) informants with the type of research and the approach used was descriptive qualitative. Data collection through the interview, observation, and documentation techniques. The data analysis technique uses data analysis techniques that include three simultaneous activities, namely data reduction, data presentation, and drawing conclusions or verification. The results showed that the management of electronic archives at the office of PT. Jasa Raharja Makassar, Overall, it is concluded that the management of employee records is not fully electronic. This is viewed from each indicator starting from the archive arrangement indicator whose results are arranged based on the date classification code on the system, the archive storage indicator whose results show employees store data in two places, namely the application and database, the archive retrieval indicator whose results are inputted into the system. and the required files will appear, archive maintenance indicators whose results do not exist specifically to maintain this electronic archive, archive security indicators whose results are contained in the system and include part of IT tasks, archive shrinkage indicators whose results have not been carried out because the system is still new and The data is still active.